P–T evolution and tectonothermal history of metamorphic rocks in Nam Dinh, the southeasternmost part of the Day Nui Con Voi metamorphic complex, Northern Vietnam - Kitano, Ippei; Vuong Bui Thi, Sinh (Vietnam Journal of Earth Sciences, 2025)
The Day Nui Con Voi high-grade metamorphic complex (DNCV) in northern Vietnam is considered the southeastern part of the Red River Shear Zone (RRSZ), a major tectonic boundary between the South China and Indochina Blocks. This study investigated minor outcrops in Nam Dinh, at the southeasternmost part of the complex, which are deficient in petrological research. It aims to establish the tectonic evolution based on the petrographic and structural features of pelitic schists and gneisses. Apart from sandstones found in the northern part, the petrographic observations reveal the metamorphic zonation from the chlorite zone, through the biotite-muscovite zone, to the sillimanite zone, progressing eastward with increasing metamorphic grade. The prominent subhorizontal mylonitic foliation (S2) folded by later open fold composes doming structure in study area. Pre-S2 microstructures (S0 and S1) and post-S2 myrmekite are also preserved. Geothermobarometric analyses of a pelitic schist in the chlorite zone and a gneiss in the sillimanite zone indicates a clockwise pressure-temperature path. The estimated metamorphic geothermal gradients are 20–25℃/km during the prograde stage, 30℃/km at peak granulite-facies metamorphism and ca. 60℃/km during retrograde conditions with the myrmekite formation. The petrological and structural characteristics are well comparable to those of the main body of the DNCV and the contemporaneous Bu Khang Dome (BKD). The combining thermal histories of the DNCV and the East Sea opening suggest the following regional tectonic evolution during Eocene-Oligocene. The Himalayan orogeny caused the crustal thickening in the DNCV and BKD on the prograde stage. Initial extensional magmatism and crustal thinning due to the onset of the East Sea opening in the back-arc setting triggered the granulite-facies metamorphism with extensive crustal anataxis, producing numerous syn-metamorphic leucogranites in the lower crust. Subsequent East Sea opening resulted in the extensional regime accompanied by the subhorizontal ductile deformation in the DNCV, and possibly in the BKD and the RRSZ. Crustal strike-slip shearing took place along the thinned and weakened anatectic crust and uplifted their metamorphic rocks with doming structure toward greenschist-facies upper crust. This process may have been correlated with the southward ridge jump of the East Sea.